Metformin versus insulin therapy for gestational diabetes: Effects on offspring anthropometrics and metabolism at the age of 9 years: A follow-up study of two open-label, randomized controlled trials - Paavilainen Elisa; Tertti Kristiina; Nikkinen Hilkka; Veijola Riitta; Vääräsmäki Marja; Loo Britt-Marie; Tossavainen Päivi; Rönnemaa Tapio; Niinikoski Harri (Wiley-Blackwell, 2022)
Aims
To compare anthropometrics, and lipid and glucose metabolism in the 9-year-old offspring of mothers treated with metformin or insulin for gestational diabetes mellitus (GDM).
Materials and Methods
This was a Finnish two-centre, 9-year follow-up study of two open-label, randomized controlled trials comparing the effects observed in the offspring of mothers who received metformin and insulin treatment for GDM. Measurements included anthropometrics, blood pressure, lipoproteins, and oral glucose tolerance tests. This study was registered with ClinicalTrials.gov, number NCT02417090.
Results
At the age of 9 years 172 children (55% of the original study cohort, 82 from the metformin and 90 from the insulin group) participated in the study. No differences were found between the 9-year-old offspring groups in anthropometric variables, including body mass index and waist-to-height ratio. The offspring in the metformin group had higher high-density lipoprotein (HDL) cholesterol concentrations (1.72 vs. 1.54 mmol/L; P = 0.039) but lower low-density lipoprotein cholesterol (2.39 vs. 2.58 mmol/L; P = 0.046) and apolipoprotein B concentrations (0.63 vs. 0.67 g/L; P = 0.043) than the offspring in the insulin group. The difference in HDL cholesterol concentration was found to be significant only in boys (P = 0.003). The 2-hour glucose value in the oral glucose tolerance test was 0.6-mmol/L lower in boys from the metformin group than in those from the insulin group (P = 0.015).
Conclusions
Metformin treatment for GDM is associated with similar offspring growth and glucose metabolism but a more favourable lipid profile at the age of 9 years as compared to insulin treatment.